CLAUDE BROWN AND THE BLACK AUTOBIOGRAPHY - Bhatti, Shaheena Ayub (European Scientific Journal, ESJ, 2015)
Harlem, New York – Promised Land for the African Americans of the post-depression period - is the focus of this essay. To the sharecroppers and field hands of the Carolinas, New York – with its infinite attractions, beckoned. Men and women tired of working from “sun-up to sun down,” were easily attracted by the promise of a fair and just city; a city which had limitless opportunities for those who wanted to live and work there. The Promised Land, for these children of African slaves, was New York, and life in New York promised freedom from chain gangs and freedom from the cotton; tobacco and sugarcane fields which had to be tilled, sowed and harvested the year round. Fields where Massa Charlie reigned supreme and to do his bidding was the ultimate aim of the plantation slaves, generations of whom had worked on these or similar plantations with no surety of keeping their families together, with no thought other than the immediate needs of the body. To these tillers of the soil, New York, post emancipation, was the Promised Land and the thought that they had arrived in the Promised Land was sufficient to hide the dirt and grime, the rampant crime and lawlessness of Harlem: named by the Dutch Protestant and Huguenot immigrants for the ‘chosen one.’ This paper seeks to explore the truth of Harlem being the Promised Land for African Americans.